Parenting Practices in Millennial Islamic Families of Pontianak: Navigating Between Pop-Islamism and Fluid Islamism - Sapendi, Sapendi; Prasojo, Zaenuddin Hudi; Ali Shah, Syed Ahmad; Munastiwi, Erni (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This qualitative study explores the parenting practices of young Islamic parents in Pontianak, Indonesia, amidst the evolving contexts of pop Islamism and fluid Islamism. The research uses anthropological lenses to focus on early childhood parenting within millennial Islamic families. The city of Pontianak, characterized by rapid development, ethnic and cultural diversity, and varied religious practices, provides a unique setting for examining these dynamics. Data collection encompassed observations, interviews, and documentation, targeting millennial Muslim parents born between 1981 and 1996, with children aged 0-8 years, totaling 83 participants. Interviews spanned a range of Islamic ideologies, including popular Islamism, tarbiyah, Tahrir, Salafi, and jihadist. The methodology involved data assembly, comprehensive observation, coding, categorization into themes, and narrative presentation. The results reveal diverse parenting patterns influenced by religious affiliations, advisors, worship practices, and explicit or implicit religious affiliations. While parenting styles varied, a high prevalence of authoritarian approaches was noted, with religion playing a pivotal role in child-rearing decisions and social interactions. The study also highlights the material aspects of parenting, including doctrinal ideologies and their manifestation in everyday life. The findings provide crucial insights into contemporary Islamic society's social and religious dynamics, emphasizing the need for an inclusive, multidimensional approach to understanding Islamism that extends beyond political and ideological realms. This research contributes to a deeper comprehension of Islamic millennial families' social and cultural intricacies in Indonesia and their strategies for balancing religious traditions with modern challenges.